EFFECTIVENESS OF USING REAL LABS AND VIRTUAL LABS TO IMPROVE SKILLS 21st CENTURY STUDENTS IN PHYSICS LEARNING - Muhammad Algi Al-Hanafi (Universitas Negeri Medan, 2025)
The 21st century requires a person to have various skills, so that the world of education is expected to be able to prepare students and also train various 21st century skills to face and overcome various problems in their future lives. In physics learning, 21st century skills can be trained through laboratory activities. Therefore, to find out more about laboratory activities, this article will present information about laboratory activities to improve 21st century skills. The method used in this article is the literature study method and the analysis is carried out based on previous research literature that is relevant to the discussion of this article. The results obtained from this article are laboratory activities, both real and virtual laboratories can be used to train students' 21st century skills, so that they are expected to improve 21st century skills. Keywords: 21st century skills, laboratory activities, physics